Determining the reliability of the reading motivation questionnaire in China / Wangyan and Muhammad Kamarul Kabilan - Wang, yan; Kabilan, Muhammad Kamarul (Universiti Teknologi MARA, Pulau Pinang, 2022)
RMQ-EFL (reading motivation questionnaire in an English as a foreign language context) was developed to explore the motivation of secondary language learners in China. This study tends to extend the samples to college learners and to determine whether they are still valid. Using the Chinese RMQ-EFL version, this study analyzed 627 data collected from two vocational colleges. After factor analysis tests in SPSS and Amos, however, a five-factor model was achieved, which was not the same as the original models done by Wang and Gan (2021). Although the various indexes made the model acceptable, the study’s limitations called for further studies to generalize the RMQ-EFL.